1987
DOI: 10.1111/j.1365-2141.1987.tb06920.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mechanism of neutropenia and thrombocytopenia in patients with human immunodeficiency virus infection

Abstract: The incidence of lymphopenia, thrombocytopenia and neutropenia was studied in 105 homosexual men with HIV infection. Lymphopenia was common in patients with AIDS (75%), but its incidence in PGL (24%) was not significantly different from that in asymptomatic anti-HIV positive (15%) homosexual men. Neutropenia and thrombocytopenia were found in patients with AIDS or PGL, but not in asymptomatic anti-HIV positive homosexuals. The study suggests that the neutropenia and thrombocytopenia in these patients were due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 17 publications
6
68
1
6
Order By: Relevance
“…29 Earlier studies indicated that platelet counts of less than 150 were more common among ART-naive patients, with prevalence figures ranging between 6% and 30% in most studies. 12,27,30 Evidence from available studies has shown that patients with anaemia have reduced survival time and accelerated HIV disease progression. For instance, an earlier study in developed countries by Mocroft et al indicated that, at 12 months, HIV patients with mild anaemia had a significantly lower survival rate than those without anaemia (84.1% vs. 96.9%), and that prognosis and survival time was even worse among severely anemic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Earlier studies indicated that platelet counts of less than 150 were more common among ART-naive patients, with prevalence figures ranging between 6% and 30% in most studies. 12,27,30 Evidence from available studies has shown that patients with anaemia have reduced survival time and accelerated HIV disease progression. For instance, an earlier study in developed countries by Mocroft et al indicated that, at 12 months, HIV patients with mild anaemia had a significantly lower survival rate than those without anaemia (84.1% vs. 96.9%), and that prognosis and survival time was even worse among severely anemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum sample size of 384 was calculated from the prevalence studies' formula by Leslie and Kish, assuming a cytopenia prevalence of 50% among ART-naive HIVpositive adults. 9,12 Consenting patients were sequentially enrolled until the sample size was reached. Pertinent patient data were recorded, including age, sex, opportunistic diseases present at the time of diagnosis, WHO clinical stage, baseline CD4 count, and most recent CD4 count.…”
Section: General Demographic Clinical and Laboratory Characteristicmentioning
confidence: 99%
“…el rol del síndrome de inmunodeficiencia adquirida (SIDA) en las IOs no es claro, ya que los estudios no muestran una mayor incidencia de Ios severas en estos pacientes 25 . sin embargo, un número significativo de pacientes con sIDa desarrollan neutropenia como consecuencia de la infección retroviral directa, el uso de medicamentos antirretrovirales, infecciones sistémicas y los mecanismos autoinmunes alterados 26 . además, los neutrófilos de pacientes con SIDA tienen su función bactericida y quimiotáctica deficiente 27,28 .…”
Section: Compromiso De La Vía Aéreaunclassified
“…1 Thrombocytopenia associated with viral infections is often caused by the generation of antiplatelet antibodies, with subsequent accelerated platelet clearance, or by the suppression of megakaryopoiesis. 3,4 However, a significant percentage of patients with infection-induced thrombocytopenia have no evidence of DIC, antiplatelet antibodies, or bone marrow suppression. 1,[5][6][7] One proposed model for thrombocytopenia during infections involves the formation of platelet-microbe complexes, followed by the clearance of these complexes from the circulation.…”
Section: Introductionmentioning
confidence: 99%